2021
DOI: 10.21203/rs.3.rs-712354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spirituality and other factors associated with COVID-19 Vaccine Acceptance amongst Healthcare Workers in Cameroon

Abstract: Background: The production of the different COVID-19 vaccines has offered hope towards controlling the pandemic. Many governments around the world have been able to secure the number of doses required for the vaccination of their entire population. In Cameroon, the government’s strategy has been to secure the number of doses required to vaccinate frontline workers and other population at risk. A threat to this strategy could be vaccine hesitancy as demonstrated in previous studies. In this article we discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Our estimates of vaccine hesitancy among HCWs were similar to other studies conducted in HCWs in Cameroon [22], Ethiopia [23], Saudi Arabia [24] and the United Kingdom [25]. However, we observed a much higher proportion of COVID-19 vaccine hesitancy than in a previous report among HCWs in South Africa [26].…”
Section: Discussionsupporting
confidence: 86%
“…Our estimates of vaccine hesitancy among HCWs were similar to other studies conducted in HCWs in Cameroon [22], Ethiopia [23], Saudi Arabia [24] and the United Kingdom [25]. However, we observed a much higher proportion of COVID-19 vaccine hesitancy than in a previous report among HCWs in South Africa [26].…”
Section: Discussionsupporting
confidence: 86%
“…The current systematic review and meta-analysis identified 8 main reasons for COVID-19 vaccine hesitancy among HCWs in Africa. These includes: the side effects of the vaccine [ 7 , 15 , 23 , 26 , 28 , 29 , 32 , 36 , 37 , 40 ] the vaccine’s safety [ 15 , 23 , 24 , 26 , 36 , 37 , 40 ], efficacy and effectiveness [ 7 , 26 , 28 , 29 , 32 , 36 , 40 ], short duration of the clinical trials [ 23 , 26 , 29 , 32 , 37 , 40 ], COVID-19 infections [ 15 , 32 ], limited information [ 27 , 28 ], and lack of social trust [insufficient trust in the vaccine’s source, lack of trust from the manufacturers, lack of trust from governments] [ 27 , 37 ]. The results are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…31 Among the 58 articles, nine studies reported $ 80% 26,27,31,32,36,[53][54][55][56] of their participants would accept/take the COVID-19 vaccine when available, 27 studies reported between 50% and 79%, [28][29][30][34][35][36]46,47,51,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and 15 studies reported , 50%. 36,45,49,50,52,[74][75][76][77][78][79][80][81][82] Of 58 studies, 31 reported factors that influence the desire to be vaccinated and were grouped as ...…”
Section: Resultsmentioning
confidence: 99%